2021
DOI: 10.1167/iovs.62.2.41
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Gene Therapy Associated Uveitis Following Intravitreal Adeno-Associated Virus Injection in Mice

Abstract: Purpose To characterize the intraocular immune cell infiltrate induced by intravitreal adeno-associated virus (AAV) gene therapy. Methods AAV vectors carrying plasmids expressing green fluorescent protein under the control of PR2.1 were injected intravitreally into AAV naive and AAV primed C57Bl/6 mice. Clinical inflammation was assessed using optical coherence tomography. Intraocular immune cell populations were identified and quantified by flow cytometry on days 1, 7,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 32 publications
0
19
0
1
Order By: Relevance
“…Following an intravitreal injection, a dose dependent immune response is observed presenting as cells in either the anterior chamber and/or the vitreous. Both cellular and humoral factors have been implicated ( 45 47 ). In mice, an AAV injection into the vitreous leads to a transient mild spontaneously resolving inflammation but the total number of CD45+ T cells remains elevated, even weeks after the injection.…”
Section: Immune Consequence Of Subretinal and Intravitreal Deliverymentioning
confidence: 99%
See 2 more Smart Citations
“…Following an intravitreal injection, a dose dependent immune response is observed presenting as cells in either the anterior chamber and/or the vitreous. Both cellular and humoral factors have been implicated ( 45 47 ). In mice, an AAV injection into the vitreous leads to a transient mild spontaneously resolving inflammation but the total number of CD45+ T cells remains elevated, even weeks after the injection.…”
Section: Immune Consequence Of Subretinal and Intravitreal Deliverymentioning
confidence: 99%
“…In mice, an AAV injection into the vitreous leads to a transient mild spontaneously resolving inflammation but the total number of CD45+ T cells remains elevated, even weeks after the injection. Both innate and adaptive immunity play a role regardless of prior immune status ( 45 ). A patient treated for Lebers with a single intravitreal dose of 9 × 10 10 vg and high pre-treatment titers of IgG neutralizing antibodies to AAV2, developed a significant post-injection ocular inflammation ( 46 ).…”
Section: Immune Consequence Of Subretinal and Intravitreal Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…One general concern for AAV vectors is that pre-existing immunity and subsequent induced adaptive immunity following vector administration can significantly reduce retinal gene expression, as shown in pre-clinical studies [ 82 ]. Furthermore, there is growing appreciation for the risk of gene therapy associated uveitis following AAV administration, which appears to be related to the vector dose and route of administration [ 83 , 84 ]. However, optogenetic clinical trials thus far have demonstrated that intravitreal delivery of AAV-based vectors is mostly safe and well-tolerated [ 8 ].…”
Section: Using Optogenetics In Retinal Degeneration and Glaucomamentioning
confidence: 99%
“…Although there are several reports linking AAV ocular gene therapy to an immune/inflammatory response, especially at high doses, no adverse effects were reported following AAV-HLA-G subconjunctival, intracorneal, or intravitreal dosing [ 14 , 15 , 16 , 42 , 55 , 56 , 57 , 58 ]. Another concern for ocular gene therapy is the durability of the transgene expression following ocular delivery.…”
Section: Hla-g and The Eyementioning
confidence: 99%